PENGARUH MOTIVASI DAN DISIPLIN KERJA KARYAWAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PT. PEGADAIAN SYARIAH SOLO BARU - Denny Adi Prasetya; M Farid Wajdi (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effect of work motivation and discipline on job satisfaction and employee performance at PT Pegadaian Syariah Solo Baru. A quantitative approach was used, with data analyzed through PLS-SEM using SmartPLS software. Data were collected from 150 employees via online questionnaires. The results show that work motivation has a positive and significant effect on both job satisfaction and employee performance. Likewise, work discipline has a positive and significant effect on job satisfaction and is the most dominant factor influencing employee performance. The R-square values indicate strong predictive power of the model, and the validity and reliability tests confirm the consistency of the research instruments. These findings highlight the importance of implementing motivation programs and strengthening work discipline as strategies to enhance employee performance and job satisfaction in Islamic-based financial institutions.